A silver nanowire mesh overcoated protection layer with graphene oxide as a transparent electrode for flexible organic solar cells. Issue 83 (15th November 2017) - Wang, Byung-Yong; Lee, Eung-Seok; Oh, Young-Jei; Kang, Hyun Wook
Abstract : AgNW mesh protected by graphene oxide (GO) is fabricated for flexible organic solar cells. GO/AgNW mesh induces intense light scattering due to surface plasmon effect and improves organic solar cell performance by enhancing light trapping effect. Abstract : For high-throughput flexible electronic devices to be ready for the market, their transparent conductive electrodes (TCEs) should show stable working performance during folding conditions and have a long operating life. In this study, TCEs were produced by over-coating silver nanowire (AgNW) electrodes with graphene oxide (GO). The GO/AgNW electrodes showed an outstanding sheet resistance value of 18 Ω −1, 87% transmittance, mechanical stability, and excellent long-term stability. Furthermore, the GO film wrapped around the AgNWs, which improved the inter-nanowire junction resistance and lowered the surface roughness without any heat treatments or high-force pressing processes. Flexible P3HT:PC60 BM- and PTB7:PC70 BM-based organic solar cells (OSCs) were produced using the GO/AgNW transparent electrodes on a flexible polyethylene terephthalate substrate. The GO/AgNW electrode exhibited a higher optical absorption in all the OSCs compared to those of the indium tin oxide (ITO) electrodes and showed a high short circuit current of 3 mA cm −2 . Consequently, the fabricated OSCs showed a 7% higher efficiency than the ITO electrodes. In addition, after 50 bending tests, the efficiency of the GO/AgNW electrodes changed less than 3%. Thus, the GO/AgNW electrodes showed enhanced results in terms of resistance and durability compared to conventional transparent electrodes, including ITO-based electrodes.